2020
DOI: 10.1038/s41598-020-69472-3
|View full text |Cite
|
Sign up to set email alerts
|

Methyl-donor supplementation prevents intestinal colonization by Adherent-Invasive E. coli in a mouse model of Crohn’s disease

Abstract: Deficiencies in methyl-donor molecules (folate, B12 vitamin), DNA methylation alteration and high prevalence of Adherent-invasive Escherichia coli (AIEC) are frequently observed in Crohn's disease (CD) patients. Aiec bacteria adhere to the enterocytes through abnormally expressed carcinoembryonic antigen-related cell adhesion molecule 6 (CEACAM6) glycoprotein on host cells. This work aims at studying the relationship between methyl-donor molecules and AIEC-induced intestinal inflammatory response. CEABAC10 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 63 publications
(91 reference statements)
0
11
0
Order By: Relevance
“…FA is a kind of methyl-donor. A previous study found that methyl-donor supplemented diet prevents the colonization of intestinal E. coli in a mouse model of Crohn’s disease, which may be by influencing the DNA methylation level of CEACAM6 gene (a kind of cell adhesion molecule) [ 65 ]. Similarly, in mice, FA supplementation prevent Helicobacter-associated gastric cancer by increasing global DNA methylation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…FA is a kind of methyl-donor. A previous study found that methyl-donor supplemented diet prevents the colonization of intestinal E. coli in a mouse model of Crohn’s disease, which may be by influencing the DNA methylation level of CEACAM6 gene (a kind of cell adhesion molecule) [ 65 ]. Similarly, in mice, FA supplementation prevent Helicobacter-associated gastric cancer by increasing global DNA methylation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a lack of methyl donors can affect the differentiation and barrier functions of the small intestine and increase the concentration of Hcy, which subsequently promotes oxidative stress and activates interrelated pro-inflammatory mechanisms, ultimately aggravating inflammatory bowel disease in rats ( 13 , 33 ). MET supplementation through the diet limits pathobiont colonization of the gut via inducing a specific intestinal micro-environment ( 11 ). When the harmful bacteria decrease, the beneficial bacteria may increase relatively.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is increasing evidence that microbiota-derived metabolites are key factors regulating animal metabolism, growth, and development ( 10 ). Maternal-MET supplementation induces a specific intestinal microenvironment, limiting pathobiont colonization [such as adherent-invasive Escherichia coli (AIEC)] of the offspring gut ( 11 ). Conversely, other studies report that maternal-MET supplementation or deficiency leads to an increase in the sensitivity to colitis in the offspring ( 12 , 13 ), suggesting the central role of MET in the intestinal microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…In a mouse model of Crohn's disease (CD), methyl-donor supplementation can prevent the intestinal colonization of adherent-invasive E. coli, showing beneficial effects on the inflammation. Furthermore, the serum folate concentration was found to be inversely correlated to fecal inflammatory markers in a cohort of CD [59]. MD supplementation during pregnancy increased the odds of colitis infection in offspring, and was found to be associated with persistent epigenetic and intestinal microbial changes [57].…”
Section: Factors Involved In the Progress Of Colitismentioning
confidence: 92%